Activated cement clinker catalyst development for biodiesel production - Shahid, Ali (2013)
World oil and gas output is expected to pass its peak in the next few years, while demand will go on rising. Renewable sources of energy (e.g. Algae biomass and agricultural crops) can make an important contribution to secure sustainable and diverse energy supplies and are therefore an essential element of a cost-effective climate change program. For now, renewable energy from biodiesel has been touted as one of the most promising substitutions for petroleum-derived diesel. Production of biodiesel is also a proven technology with established commercialization activities. Combustion of biodiesel as fuel is more environment-friendly while retaining most of the positive engine properties of petroleumderived diesel. Currently, the commercially used catalysts like Sodium Hydroxide (NaOH), Potassium Hydroxide (KOH) etc, has given birth to problems like expensive availability, non-recyclability, complex recovery system and saponification problems. Secondly, biodiesel production from edible has being directly contributing to the high costs of vegetable oils. Based on high composition of CaO in the calcinated product of limestone it is selected as the potential candidate for biodiesel production in this research. This research model helps to create a better understanding and awareness towards the value and the importance of using an insoluble heterogeneous Activated Cement Clinker Catalyst (ACCC), with a simple activation process that avoids the saponification problem , easily recoverable from a reaction mixture without washing or neutralization and the catalytic activity is not negatively affected by the free fatty acids and the catalyst material is easily recycled for use in subsequent catalytic reactions. The catalyst after dispersing in methanol and thermal activation shows immense increase in the surface area. The research was being carried out to analyze the effect of ACCC on conventional and microwave assisted biodiesel production. The ideal reaction conditions to get 96.80% of conversion were methanol to oil, molar ratio, 5:1; catalyst concentration used, 6 wt %; reaction temperature of 55°C and retention time of 50 mins for microwave assisted transesterification (MAT), while, at temperature of 60°C and a retention time of 80 min for conventional method from rubber seed oil (RSO). Catalyst analyzed for surface area by Surface Analyzer shows a decline in its surface area as the catalyst proceeds through recycling and reusing process, with surface area of 59.5 m 2 /gm at the first cycle and 13.54 M2 /gm at the fifth cycle. The biodiesel produced is within the limits being described by ASTM D 6571.